A Synthetic and Structural Study of Arylselenoamides and 2,4-Diaryl-1,3- Selenazoles - Hua, Guoxiong; Du, Junyi; Slawin, Alexandra M. Z.; Woollins, J. Derek (Synlett, 2014)
The systematic preparation of 2,4-diaryl-1,3-selenazoles was carried out by two-component cyclization of the primary selenoamides with α-halo ketones. Selenoamides were obtained from the reaction of Woollins’ reagent with arylnitrile, followed by hydrolysis with water. Three selenoamides have close structural similarities along with intermolecular interactions such as the strong N–H···O hydrogen bonding, the weak N–H···Se, C–H···O/N/Se intermolecular interactions and π–π stacking interactions; meanwhile, the newly formed five-membered N–C–Se–C–C rings in ten 2,4-diaryl-1,3-selenazoles have either planar or near-planar conformations along with the weak C–H···O/N/Se/Br/Cl intermolecular interactions and π–π stacking interactions. In addition, the weak Se···Se close contacts in four cases and the C–H···N intramolecular interactions in two structures were also observed within the all solid structures.
Keywords: selenoamides; 1,3-selenazoles; Woollins’ reagent; X-ray crystal structures; α-halo ketones